GRAMMATICAL FAULTS OF GOOGLE TRANSLATE IN TRANSLATING ANDREA HIRATA’S LASKAR PELANGI - Karmila Indah Khasanah Huda; Erna Nurkholida (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Nowadays, Google Translate is a common online tool to help people translate one language to other languages. It makes the translation quality of Google Translate very important. Therefore, this study aimed to investigate grammatical faults resulting from Google Translate based on Dulay's theory and discover the possible causes of grammatical faults in translating the Laskar Pelangi novel in Google Translate. Thirty-seven sentences related to the physical condition of the school were chosen, translated into English by Google translate, and analyzed qualitatively by using content analysis. The results showed that 205 errors were found, consisting of 48.29% misformation, 23.41% omission, 17.07% addition, and 11.21% disordering. These errors were caused by the improper structure of the source language affecting the Google Translate system in translating sentences, word by word translation, and the lack of awareness of Google Translate users in reviewing the translation results from Google Translate. The results also revealed that the errors in translating the novel and corpus were suitable. Regardless of the translation suitability of Google Translate in translating corpus shown by several studies, the findings also proved that research on the grammatical errors of novel translations was still lacking.